The Rise and Fall of the Political Press in Britain - Koss, Stephen; Edited By Stephen Koss (London Fontana Press, 1990)
A review of the history of the press in Britain from the middle of the 19th century, placed in a political setting. In the process, Koss unravels the Byzantine networks of relationships that have existed between politicians and newspapermen since the Victorian age.
Include Index, Manuscripts Source, and Coloured Illustrations.
Keywords: Press and Politics -- Press and Politics -- Great Britain -- History